The Analysis of Environmental Performance to Moderate The Effect of Financial Performance on Firm Value - Eti Yustika Hartono; Hadi Pramono; Edi Joko Setyadi; Annisa Ilma Hartikasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine how the impact of the implementation of Financial Performance on Firm Value with Evironmental Performance as a moderating variable. The population of this study is all companies listed on Bursa Efek Indonesia in 2019-2021. The sample has been determined by purposive sampling technique, the predetermined criteria was successful obtained 63 of sample companies listed on Bursa Efek Indonesia and obtained a PROPER rating. Data were analyzed using Moderating Regression Analysis. The result of this research indicated that : 1) ROA has a negative effect on firm value, 2) ROE has a positive effect on firm value, 3) Environmental performance is able to moderate ROA on firm value, 4) Environmental Performance unable to moderate ROE on firm value.